청소년 자녀가 지각한 부부갈등이 또래괴롭힘에 미치는 영향 : 자기체계손상과 폭력허용도의 이중매개효과 - 김수정(Su Jeong Kim); 김정민(Jung Min Kim); 황인희(In Hee Hwang) (Korean Journal of child studies, 2019)
Objectives: This study’s purpose was to examine the effects of marital conflicts perceived by adolescents on self-system traumatization, violence tolerance, and bullying. Additionally, the dual mediating effects of self-system traumatization and violence tolerance on the relationship between marital conflicts perceived by adolescent children and bullying were examined. Methods: Participants were middle and high school students in Seoul and Gyeonggi-do, who had experienced bullying. Data analysis was conducted through descriptive statistics using SPSS Statistics 21.0 and the separate and dual mediating effect analyses were conducted using SPSS Marco. Results: Both self-system traumatization and violence tolerance had a partial mediation effect on the relationship between marital conflicts perceived by adolescent children and bullying. Moreover, self-system traumatization and violence tolerance had a full dual-mediation effect on the relationship between marital conflict perceived by adolescent children and bullying. Conclusion: The results indicate to provide preventive data on adolescents who harassed their peers by looking at the dual mediating effects of self-system traumatization and violence tolerance based on the relationship between marital conflict and bullying. KCI Citation Count: 2